Body composition in students physical education and sport: cross-sectional pilot study - Ratko Pavlović (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Purpose: Young people who study physical education and sport are a priori regarded as having proper body structure and body composition. It is widely presumed that young who study physical education at one of several national universities of physical education (East Sarajevo) could be characterized with proper physique and body composition. Aim of the current study was to assess and analyze the body composition of a male students Physical Education and Sport, University East Sarajevo, by bioelectric impedance analysis and determine the significance of inter correlation coefficients. Material and methods: In study the participants consist 30 male students of Faculty of Physical Education and Sport, University of East Sarajevo, the III year of study (Body Height = 182.20 ± 6.89cm; Body Weight = 80.06 ± 8.80kg; Body Mass Index= 24.03 ± 2.58kg/m²). Results: of the study showed that the body composition is within the healthy (allowed) values recommended for this population of students (Body Fat=10.90kg or 13.62%; Body Muscle= 65.74kg or 82.40%; Body Water = 61.54%; Basal metabolic rate = 2045.07kCal; Daily calorie intake = 8436.56 kCal, etc.). Inter correlation coefficients showed inverse and significantly high correlation (p=0.000) between (inter correlation coefficient Fat-Muscle = -0.945), (inter correlation coefficients Fat-Water = -0.963) while direct correlation was achieved between (inter correlation coefficient Muscle-Water = 0.986). Conclusion: The obtained results of the study defined the appropriate body composition of the students, which is a consequence of their adequate physical activity and well-designed curricula at the home faculty. In the parameters of body composition, students of physical education and sports in East Sarajevo had a higher muscle component and lower values ​​of fat component than other students as a result of their somatotype, way of studying, teaching and extracurricular physical activities.